The Influence of Need-Supportive Teacher Behavior on the Motivation of Students with Congenital Deafblindness. (May 2017) - Haakma, Ineke; Janssen, Marleen; Minnaert, Alexander
Introduction: Research has indicated that need-supportive learning environments positively influence students' motivation. According to self-determination theory, a need-supportive learning environment is one in which teachers provide structure, autonomy support, and involvement, and thereby support their students' psychological needs for competence, autonomy, and relatedness. In this study, we aimed to explore whether teachers of students with congenital deafblindness provide such an environment and how they adjust their need-supportive teaching to these students. Methods: We conducted an in-depth analysis of teacher-student interactions using a multiple-case-study design. We analyzed videos of teacher-student interactions from the perspective of self-determination theory. Results: We found that successful need support for this group requires careful adjustments for each individual student. Only if the provision of structure, autonomy support, and involvement is tailored to the student can a positive influence on motivation be noticed. Another important finding is that teachers provide more structure and involvement than autonomy support. Discussion: This study showed that need-supportive teaching is important in the education of students with congenital deafblindness. By using video analysis, we were able to point out teaching strategies that led to greater motivation for these students. Implications for practitioners: Motivation is a prerequisite for learning, and teachers' behavior might add to that motivation. This study showed that need support leads to enhanced motivation in students with congenital deafblindness. We provided practical insights that teachers can use to create need-supportive learning environments for these students.